FRAME REPRESENTATION OF THE CONCEPT DEATH/O’LIM /ÓLIM - Ganieva, Zukhra (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
This study explores the conceptual representation of death in English, Uzbek, and Karakalpak cultures through a frame analysis of the lexeme death. Using English thesauruses and cultural sources for Uzbek and Karakalpak languages, it examines how each culture categorizes death within unique slots: Causes, Funeral, Attributes, Participants, Places, and Services. English-speaking cultures emphasize secular and personal approaches, with diverse funeral types, while Uzbek and Karakalpak cultures hold more religious and communal perspectives governed by Islamic principles. The frame analysis reveals both universalities in causes (natural, accidental, intentional) and cultural divergences, such as attitudes toward practices like euthanasia, post-funeral rituals, and body preparation. This cross-cultural study provides insight into how beliefs, social values, and historical practices influence the perception and handling of death, underscoring its role in cultural identity and community integrity.
Keywords: concept death; cultural frame analysis; funeral traditions; English culture; Uzbek culture; Karakalpak culture; funerary rites; rituals; cultural identity